Kualitas Pelayanan Publik Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Seram Bagian Barat - Vivi Fitrianty Umasugi (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Quality public services are called the best services that meet service quality standards. The best service standards that meet service quality standards are benchmarks that are used as guidelines for service delivery and service quality assessment references as service obligations to the community in the context of quality services. This research is about the Achievement of Public Service Quality at the Civil Registration Office of Seram Bagian Barat Regency, which uses a descriptive qualitative approach, a descriptive qualitative approach decides on a particular unit, where the problem is examined comprehensively, in detail, and various in-depth variables are then examined and made, including the possible relationship between existing variables. To realize quality public services, it is necessary to increase satisfaction with the community. The appearance and ability of physical facilities and infrastructure with the surrounding environment is tangible evidence of a service provided by service providers including the physical facilities of the service place, the equipment used, and the appearance of employees in serving the community. To improve the quality of service at the Population and Civil Registration Office of Seram Bagian Barat Regency, researchers suggest that: Disdukcapil of West Seram Regency should add service support facilities or service infrastructure, for example by adding chairs and putting fans or air conditioners and providing reading books, newspapers, or magazines in the waiting room.